Book review: These are our bairns: A guide for community planning partnerships on being a good corporate parent. The Scottish Government. - Irene Stevens (Scottish Journal of Residential Child Care)
The term 'corporate parent' has been used with increasing frequency. But what do we mean when we talk about a 'corporate parent'? This short guidance document is designed to provide some answers to this question in a Scottish context. Written as a user-friendly guide to corporate parenting, it acknowledges the importance of partnership between agencies in order to deliver the best experience for the looked-after child.